(3GdYedjGJ GdeUQajI GdNGQLjI (B/s - (3TcQj, eGgQs ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2004)
(3GdYdGbGJ GdeUQajI GdNGQLjI, GJaGbjI GdJYGed eY GdHfhc GdeQGSdI, GOGQI GdYdGbGJ eY GdHfhc, GdMhGOK GdNGQLjI , GdTjcGJ HGdYedGJ GdCLfHjI hChQGb GdfbO GdCLfHj, GdUYhHGJ GdeSJfOjI, GdJMUjd GdeSJfOj, Jehjd GdJHGOd GdJLGQj HhGSWI GdJMUjd GdeSJfOj, GOGQI YedjGJ GdJMUjd GdeSJfOj, GdbhGYO GdehMOI ddJMUjd, GdGYJeGOGJ GdeSMjI, Jehjd GdJHGOd GdJLGQj GdOhdj HhGSWI GdGYJeGOGJ GdeSJfOjI, GdCUhd hGdCYQGa GdehMOI GdGYJeGOGJ GdeSJfOjI, GOGQI YedjGJ GdGYJeGOGJ GdeSJfOjI, caGdGJ GdYbhO GdJLGQjI, OhQ GdcaGdGJ aj GdJHGOd GdJLGQj, GOGQI YedjGJ caGdGJ GdYbhO GdNGQLjI(B.s
(3GdeQGLY U(B.491s
Keywords: (3GdHfhcs; (3GdSfOGJs; (3GdeUGQjas